2008
DOI: 10.1001/archopht.126.10.1434
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Improve the Accuracy of Vision Measurement by Teachers in Rural Chinese Secondary Schoolchildren

Abstract: To assess and improve the accuracy of lay screeners compared with vision professionals in detecting visual impairment in secondary schoolchildren in rural China. Methods: After brief training, 32 teachers and a team of vision professionals independently measured vision in 1892 children in Xichang. The children also underwent vision measurement by health technicians in a concurrent government screening program. Results: Of 32 teachers, 28 (87.5%) believed that teacher screening was worthwhile. Sensitivity (93.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 37 publications
(46 reference statements)
6
25
4
Order By: Relevance
“…However, our final number of trained teachers was within the range reported in other programs (11, 14) and remains sufficiently large to draw conclusions as expected in a pilot intervention.…”
Section: Discussionsupporting
confidence: 69%
“…However, our final number of trained teachers was within the range reported in other programs (11, 14) and remains sufficiently large to draw conclusions as expected in a pilot intervention.…”
Section: Discussionsupporting
confidence: 69%
“…For example, Sharma et al (2008) has shown that after a brief training session from a clinician, teachers can successfully and accurately take on the burden of screening children for vision problems in their classes or schools, and refer non-passing children to specialists in the county seat for further examination. Sharing the screening burden with teachers based locally nearly eliminates the need for clinicians to travel to distant schools to provide this first level of care.…”
Section: Resultsmentioning
confidence: 99%
“…In Iran, for instance, the sensitivity and specificity of teachers' screenings are 37.5% and 92% (at the 20/25 cut-off); in China, the rates are 93.5% and 91.2% (at the 6/12 or 20/40 cut-offs); and in Tanzania, the rates are 80% and 91% (at the 6/12 or 20/40 cut-offs) [4], [23], [24]. No other study, however, has examined teacher-conducted screening in pre-primary school children; this is the first study evaluating the feasibility and accuracy of non-health professionals screening for refractive errors in this population group.…”
Section: Discussionmentioning
confidence: 99%